The influence of alkali activators on the properties of ternary blended cement incorporated with ferronickel slag. (7th February 2022) - Jae Kim, Min; Ik Hwang, Woong; Jung Cho, Won
Highlights: The setting time and adiabatic temperature of binary and ternary blended cement mixed with FNS or/and PFA was assessed. The hydration in blended cement with NaOH and KOH alkali activator was confirmed by XRD, TGA and SEM. Nano sized CH was formed at ternary blended cement with NaOh alkali activator. Nano sized CH was formed at ternary blended cement with NaOh alkali activator. Abstract: In this study, the influence of alkali activators on the properties of blended cement containing pulverized fly ash (PFA) or/and ferronickel slag (FNS) powder was investigated. As a binder, ordinary Portland cement (OPC), PFA, and FNS were used to produce alkali-activated blended mixes; OPC and ternary mix, including two different types of admixtures, respectively. Setting time, adiabatic temperature rise, and development of compressive strength was evaluated for physical performance. Hydration characteristics of the blended pastes with hydroxide activators were analyzed by x-ray diffraction, thermogravimetric analysis, and scanning electron microscope. It was found that blended cement containing FNS as the binder can prolong the setting time and hydration heat which was substantially mitigated due to a latent hydration characteristic. In terms of geopolymerization, the formation of hydration products was enhanced in ternary blended cement, which showed the highest compressive strength in the long-term curing.